Methionine oxidized apolipoprotein A-I at the crossroads of HDL biogenesis and amyloid formation - Witkowski, Andrzej (FASEB J, 2018)
Apolipoprotein A-I (apoA-I) shares with other exchangeable apolipoproteins a high level of structural plasticity. In the lipid-free state, the apolipoprotein amphipathic α-helices interact intra- and intermolecularly, providing structural stabilization by self-association. We have reported that lipid-free apoA-I becomes amyloidogenic upon physiologically relevant (myeloperoxidase-mediated) Met oxidation. In this study, we established that Met oxidation promotes amyloidogenesis by reducing the stability of apoA-I monomers and irreversibly disrupting self-association. The oxidized apoA-I monomers also exhibited increased cellular cholesterol release capacity and stronger association with macrophages, compared to nonoxidized apoA-I. Of physiologic relevance, preformed oxidized apoA-I amyloid fibrils induced amyloid formation in nonoxidized apoA-I. This process was enhanced when self-association of nonoxidized apoA-I was disrupted by thermal treatment. Solid state NMR analysis revealed that aggregates formed by seeded nonoxidized apoA-I were structurally similar to those formed by the oxidized protein, featuring a β-structure-rich amyloid fold alongside α-helices retained from the native state. In atherosclerotic lesions, the conditions that promote apoA-I amyloid formation are readily available: myeloperoxidase, active oxygen species, low pH, and high concentration of lipid-free apoA-I. Our results suggest that even partial Met oxidation of apoA-I can nucleate amyloidogenesis, thus sequestering and inactivating otherwise antiatherogenic and HDL-forming apoA-I.—Witkowski, A., Chan, G. K. L., Boatz, J. C., Li, N. J., Inoue, A. P., Wong, J. C., van der Wel, P. C. A., Cavigiolio, G. Methionine oxidized apolipoprotein A-I at the crossroads of HDL biogenesis and amyloid formation.